Topical issues of political science in the context of social modernization of Kazakhstan (Journal of Philosophy Culture and Political Science, 2019)
In article «Pressing issues of Political Science within the context of social modernization of Ka-zakhstan» the main tasks of political science within the framework of social transformation are con-sidered. Political scientists of Kazakhstan should answer the contemporary issue : how government should transform its social policy, fi rst of taking into consideration the creating of all the conditions for self-realization of its citizens and providing of their basic life standards. Keywords: social modernization, political science, public policy, political process.